Neuroimmunomodulation of natural killer (NK) cells by ergot alkaloid derivatives - Fiserová, A; Kovárů, H; Hajduová, Z; Mares, V; Starec, M; Kren, V; Flieger, M; Pospísil (Physiological research, 1997)
Ergot alkaloids (EAs), products of Claviceps spp., are widely used in various fields of clinical medicine (neurology, psychiatry, endocrinology). In the present work we studied the neuroimmunomodulative effect of EAs on activation of NK cells and their signalling pathways. Furthermore, the killing capability of rat NK cells in vitro was examined in the presence of glycosidic derivatives of elymoclavine, agroclavine, and liposome-encapsulated EAs. The engagement of appropriate NK cell membrane receptors by EAs cause an indirect enhancement of adenylyl cyclase system through inhibition of G-protein al,2-subunit (up to 50 % of control values). All of the tested EAs enhanced the rat NK cell-mediated cytotoxic activity in vitro, particularly against target cells of astrocyte origin (C-6 glioma). The present results argue for a possible EA immunomodulatory role of cell-mediated immunity in tumour regression processes.
Keywords: kultivované buňky; cytotoxicita imunologická; myši; signální transdukce; nádorové buňky kultivované; Cells, Cultured; námelové alkaloidy; buňky NK; Cytotoxicity, Immunologic; Rats; Killer Cells, Natural; Ergolines; lidé; Signal Transduction; neuroimunomodulace; Humans; buněčné dělení; liposomy; Mice; Ergot Alkaloids; monocyty; Animals; Oligosaccharides; Monocytes; ergoliny; Neuroimmunomodulation; zvířata; Cell Division; Liposomes; Claviceps; oligosacharidy; krysa rodu Rattus; lékové transportní systémy; Tumor Cells, Cultured; Drug Delivery Systems